2010
DOI: 10.2176/nmc.50.45
|View full text |Cite
|
Sign up to set email alerts
|

Vernet's Syndrome Caused by Large Mycotic Aneurysm of the Extracranial Internal Carotid Artery After Acute Otitis Media -Case Report-

Abstract: An 85-year-old man presented with a rare large aneurysm of the extracranial internal carotid artery (ICA) due to acute otitis media manifesting as Vernet's syndrome 2 weeks after the diagnosis of right acute otitis media. Angiography of the right extracranial ICA demonstrated an irregularly shaped large aneurysm with partial thrombosis. The aneurysm was treated by proximal ICA occlusion using endovascular coils. The ICA mycotic aneurysm was triggered by acute otitis media, and induced Vernet's syndrome as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…[ 1 ] Vascular causes of Vernet syndrome can be high jugular bulbs and aneurysms of the extracranial internal carotid artery or vertebral artery, as well as jugular phlebectasia. [ 13 , 15 ] Neurological diseases that can present with JFS symptoms are Guillain–Barrè syndrome, myasthenia gravis, and neuralgic amyotrophy. [ 7 , 16 ] Potential infectious causes of Vernet syndrome are Varicella–Zoster virus infection, Herpes virus infection, Haemophilus influenzae , Neisseria meningitidis , [ 1 , 7 ,] as well as parapharyngeal abscess, spreading to jugular foramen mostly caused by: Streptococcus pyogenes , Streptococcus pneumoniae , and Staphylococcus aureus .…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Vascular causes of Vernet syndrome can be high jugular bulbs and aneurysms of the extracranial internal carotid artery or vertebral artery, as well as jugular phlebectasia. [ 13 , 15 ] Neurological diseases that can present with JFS symptoms are Guillain–Barrè syndrome, myasthenia gravis, and neuralgic amyotrophy. [ 7 , 16 ] Potential infectious causes of Vernet syndrome are Varicella–Zoster virus infection, Herpes virus infection, Haemophilus influenzae , Neisseria meningitidis , [ 1 , 7 ,] as well as parapharyngeal abscess, spreading to jugular foramen mostly caused by: Streptococcus pyogenes , Streptococcus pneumoniae , and Staphylococcus aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Infections involving the carotid arteries are exceedingly rare, and these cases uniformly involve mycotic aneurysms. Recent literature reviews regarding carotid mycotic aneurysms have identified only 99 cases to date 2, 5, 6. None of these reports documented a secondary carotid plaque infection with septic emboli, without evidence of mycotic aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular occlusion of an ICA pseudoaneurysm has become a common treatment. Currently, numerous cases of successful management with coiling have been reported . Endovascular management with a covered stent has also been shown to successfully treat ICA pseudoaneurysm while preserving blood flow through the affected artery .…”
Section: Discussionmentioning
confidence: 99%
“…To date, three cases of petrous ICA pseudoaneurysm have been described as a complication of otogenic infection including one following chronic otitis media, one consequent of tuberculous otitis, and one secondary to malignant otitis externa (MOE) . One additional case of extracranial ICA pseudoaneurysm at the level of the jugular foramen has been described following an acute otitis media …”
Section: Introductionmentioning
confidence: 99%